Pembajakan Software Komputer dan Aspek Pengaturan Hukumnya - Dako, Amirudin Y. (Jurnal Pelangi Ilmu, 2008)
Identifying mark of blooming computer technology was presented by many software with the competitive of superioruty and software capabilties. Expansion of information technology is unpredictable, and followed with crime of information technology. For the present time this is carryng the problem of software piracy. The aim of this paper is analizing of computer software piracy where evaluated from the aspect of solving of law. So, basically software piracy is an badness acting in copyrights area. To overcome the boisterous of software piracy, required law peripheral which emphatically enforcement that. The role of law applied for protecting copyrights from developer of software. With law, field of information technology is strengthened so that everyone is not any doing deed impinging law